Assessment of pulmonary functions and peripheral muscle strength of COPD patients in different GOLD stages - ÜNLÜ, BEGÜM (My University, 2022)
Purpose: The purpose of this research was to examine the respiratory functions, respiratory muscle strength and peripheral muscle strength of COPD patients with different GOLD stages and to evaluate their correlation with the duration and prognosis of the disease in COPD. Methods: Patient’s demographic information, clinical status, COPD Assessment Test score, mMRC Dyspnea Scale score, emergency and hospital admissions numbers in the last three months, number of exacerbation and hospitalizations in the last one year were recorded. Maximal mouth pressures were used for respiratory muscle strength. Peripheral muscle strength was evaluated with hand grip in the upper extremity. In the lower extremity knee extension and flexion strength were evaluated with a hand-held dynamometer. The findings of PFT performed during the regular hospital controls were obtained. GOLD stages of patients were determined according to GOLD combined assessment. Results: Total of thirty-one COPD cases (five females, twenty-six males, age 64.80 ± 7.71 years), including nine in Group B, five in Group C and seventeen in Group D, were included in our study. There were statistically significant, negative, moderate correlations between all patients’ respiratory functions and disease duration (p <0.05; for FVC% r: -0.410; for FEV1 % r: -0.569; for MEF25-75% r: -0.451). There was statistically significant, moderate, negative correlation between knee extension strength and numbers of exacerbations and hospitalizations over the last one year (p <0.05). Conclusion: The results of the study suggest that non-respiratory symptoms and GOLD stages should also be considered in the planning of COPD follow-up and pulmonary rehabilitation programs. Keywords: COPD, pulmonary functions, peripheral muscle strength

Amaç: Bu araştırmanın amacı, farklı GOLD evrelerdeki KOAH hastalarının solunum fonksiyonlarını, solunum kas kuvvetlerini ve periferal kas kuvvetlerini incelemek ve KOAH’da hastalığın süresi ve prognozu ile ilişkisini değerlendirmekti. Yöntemler: Hastaların demografik bilgileri, klinik durumları, KOAH Değerlendirme Testi skoru, mMRC dispne skalası skoru, son üç ay içindeki acil servis başvuru ile hastaneye yatış sayıları, son bir yıl içindeki alevlenme öyküsü ile buna bağlı hastaneye yatış bilgileri kaydedildi. Solunum kas kuvveti değerlendirmesi için maksimal ağız içi basınç ölçümü yöntemi kullanıldı. Üst ekstremite periferal kas kuvveti dinamometre ile birlikte el kavrama kuvveti olarak değerlendirildi. Alt ekstremite periferal kas kuvveti değerlendirmesinde el dinamometresi ile diz ekstansiyon ve fleksiyon kuvveti değerlendirmesi yapıldı. Ayrıca tüm hastaların düzenli hastane kontrolleri sırasında yapılan solunum fonksiyon testi sonuçları alındı. KOAH hastalarının GOLD evrelerinin belirlenmesi GOLD birleşik değerlendirmesine göre yapıldı. Bulgular: Araştırmaya dokuz B Grubu, beş C Grubu ve on yedi D Grubu olmak üzere toplam otuz bir KOAH hastası (beş kadın, yirmi altı erkek; yaş ortalaması 64.80 ± 7.71 yıl) dahil edildi. Tüm hastaların hastalık süresi ile FVC%, FEV1 %, MEF25-75% değerleri arasında istatistiksel olarak anlamlı, negatif, orta dereceli korelasyon vardı (p <0.05; FVC% için r: -0.410; FEV1 % için r: - 0.569; MEF25-75% için r: -0.451). Ayrıca tüm hastaların diz ekstansiyon kuvveti ile son bir yıl içindeki alevlenme öyküsü ve hastaneye yatış sayısı arasında istatistiksel olarak anlamlı, negatif, orta dereceli korelasyon bulundu (p <0.05). Sonuç: Çalışmanın sonuçlarına göre, KOAH takibi ve pulmoner rehabilitasyon programlarının planlanmasında solunum dışı semptomlar ve KOAH evreleri de dikkate alınabilir. Anahtar Kelimeler: KOAH, pulmoner fonksiyonlar, periferal kas kuvveti
Farklı GOLD evrelerindeki KOAH hastalarında pulmoner fonksiyonlar ve periferal kas kuvvetinin değerlendirilmesi
Keywords: Sağlık Bilimleri; Health Sciences; Klinik Tıp (MED); Clinical Medicine (MED); COPD; pulmonary functions; peripheral muscle strength; KOAH; pulmoner fonksiyonlar; periferal kas kuvveti